Managing Scout Based Extracurricular Activities to Strengthen Student Discipline in Senior High Schools: A Case Study from Indonesia - Euis Guntur Patimah; Maman Suherman, (Journal of Science and Education (JSE), 2025)
This study explores the management of Scout-based extracurricular learning as a strategic approach to strengthening student discipline in senior high schools. Amid increasing emphasis on character education in the 21st century, Scouting offers a practical, experience-based model for fostering core values such as responsibility, time management, and self-regulation. Using a qualitative case study design, research was conducted at SMAN 6 Kota Tasikmalaya and SMAN 1 Cisayong, selected for their active Scouting programs. Data were collected through in-depth interviews, participant observations, and document analysis, and analyzed using an interactive model involving data reduction, display, and verification. The findings reveal that effective Scout learning management includes structured planning, distributed leadership, experiential implementation, and authentic evaluation. These elements contribute significantly to shaping student discipline in daily school life. Supporting factors include strong leadership, trained Scoutmasters, motivated students, and adaptive institutional strategies, while challenges such as funding constraints and limited infrastructure are addressed through creative solutions. The study concludes that Scout-based learning is a powerful and scalable model for character education when supported by collaborative ecosystems. It recommends institutional support, capacity building, and policy integration to maximize its transformative potential in school culture